Comprehensive Analysis of the Immune Infiltrates and Aberrant Pathways Activation in Atherosclerotic Plaque - Han, Hukui; Du, Rongsheng; Cheng, Panke; Zhang, Jiancheng; Chen, Yang; Li, Gang (Frontiers in Cardiovascular Medicine, 2021)
Atherosclerosis is the pathological basis of many cardiovascular and cerebrovascular diseases. Due to the development of gene chip and high-throughput sequencing technologies, the immune microenvironment of coronary artery disease (CAD) in high-risk populations has been shown to play an important role in the formation and development of atherosclerotic plaques. Based on high-throughput profiling, three gene expression datasets related to CAD were assessed. CIBERSORT analysis revealed significant differences in five types of immune cells: activated dendritic cells (DCs), T follicular helper cells (Tfhs), resting CD4+T cells, regulatory T cells (Tregs), and γδ T cells. The immune transcriptome analysis indicated higher levels of inflammatory markers (cytolytic activity, antigen presentation, chemokines and cytokines) in the cases than the controls. The level of activated DCs and the lipid clearance signaling score were negatively correlated. We observed a positive correlation between the fraction of Tfhs and the lipid biosynthetic. Resting CD4+ T cells and the activity of pathways related to ossification in bone remodeling and glutathione synthesis showed a negative correlation. Gamma delta T cells (γδ T cells) were negatively correlated with IL-23 signaling activity. GSEA revealed a close association between the inflammatory immune microenvironment. This study revealed that CAD patients may have an inflammatory immune microenvironment, suggesting that these individuals should receive personalized treatment.